Exploring factors influencing uptake and adherence to a home-based prehabilitation physical activity and exercise intervention for patients undergoing chemotherapy before major surgery (ChemoFit): a qualitative study. Issue 9 (22nd September 2022) - Cooper, Matthew; Chmelo, Jakub; Sinclair, Rhona C F; Charman, Sarah; Hallsworth, Kate; Welford, Jenny; Phillips, Alexander W; Greystoke, Alastair; Avery, Leah
Abstract : Objectives: Preoperative exercise training can improve cardiorespiratory fitness before major surgery. However, little is known about what influences participation and adherence in high-risk patient groups. We identified barriers and facilitators to uptake, engagement and adherence to a presurgical, home-based physical activity and exercise intervention called ChemoFit delivered during chemotherapy and before major oesophagogastric surgery. Design: A qualitative study using focus group discussions and individual semi-structured interviews was conducted. All were audio-recorded, transcribed verbatim and data thematically analysed. Setting: Northern Oesophagogastric Unit, Royal Victoria Infirmary, Newcastle upon Tyne NHS Hospitals Foundation Trust. Participants: Patients with oesophagogastric cancer who participated in the ChemoFit intervention recruited between March 2020 and January 2021. Intervention: A home-based physical activity and exercise intervention involving cardiovasular and strength exercise using resistance bands and pedometers to monitor step count. Weekly telephone calls provided feedback, support and positive reinforcement. Results: Twenty-two participants (18 men, 4 women; aged 67±8 years old) took part in a focus group discussion (n=17) or a semi-structured interview (n=5). Fifteen themes were identified from the data generated. Participants reported that the intervention was physically and mentally beneficial, and data highlighted features of the intervention that influenced uptake and adherence. An opportunity to increase the likelihood of surviving the pending operation was reported by participants as the most salient factor to engagement, and using the intervention as a distraction from illness and taking steps to positively influence the situation were the most salient factors to adherence. Conclusions: Uptake to the ChemoFit intervention was encouraged by provision of information that participation could reduce surgical risk and that participants could play an active role in risk reduction. Adherence was facilitated by the intervention being considered a positive distraction and participants being able to do something that could ultimately provide benefit. While participants reported difficulties and avoidance with some of the exercises recommended, understanding the importance of physical activity and exercise as part of their treatment regimen led to individual adaptations to intervention components to reach individual goals. Trial registration number: NCT04194463